2023
DOI: 10.3389/fnins.2023.1096865
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effects and duration of a short and single application of transcutaneous auricular vagus nerve stimulation on P300 event related potential

Abstract: IntroductionTranscutaneous auricular vagus nerve stimulation (taVNS) is a neuromodulatory technique that stimulates the auricular branch of the vagus nerve. The modulation of the locus coeruleus-norepinephrine (LC-NE) network is one of the potential working mechanisms of this method. Our aims were 1-to investigate if short and single applications of taVNS can modulate the P300 cognitive event-related potential (ERP) as an indirect marker that reflects NE brain activation under control of the LC, and 2-to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 128 publications
(229 reference statements)
0
3
0
Order By: Relevance
“…While we cannot provide direct neurophysiological evidence, we speculate that taVNS, through one of the neural circuits mentioned above, activated the cholinergic BF, leading to the observed enhancement of SAI. Furthermore, the observed augmentation of SAI in our study did not occur immediately after taVNS, but rather 15 minutes after its completion, suggesting that mechanisms producing after-effects (o ine effects) are involved post-stimulation, possibly related to synaptic plasticity following taVNS 51 . Fragons et al 17 in an fMRI study, reported a decrease in the observed BOLD signal enhancement in the subthalamic nucleus (STN) during taVNS, which was followed by an increase in LC activity after stimulation.…”
Section: Discussionmentioning
confidence: 46%
“…While we cannot provide direct neurophysiological evidence, we speculate that taVNS, through one of the neural circuits mentioned above, activated the cholinergic BF, leading to the observed enhancement of SAI. Furthermore, the observed augmentation of SAI in our study did not occur immediately after taVNS, but rather 15 minutes after its completion, suggesting that mechanisms producing after-effects (o ine effects) are involved post-stimulation, possibly related to synaptic plasticity following taVNS 51 . Fragons et al 17 in an fMRI study, reported a decrease in the observed BOLD signal enhancement in the subthalamic nucleus (STN) during taVNS, which was followed by an increase in LC activity after stimulation.…”
Section: Discussionmentioning
confidence: 46%
“…However, the external ear is also innervated by trigeminal nerve fibers, partially overlapping with the vagus territory [ 100 , 101 ]; therefore, an appropriate electrode positioning easily results in the stimulation of both trigeminal and vagal afferents [ 6 , 102 ]. The study of auricular tVNS has seen great development in recent years, especially with regard to improved cognitive performance, not only in the clinical population but also in healthy subjects [ 103 , 104 , 105 , 106 , 107 ]. While the neurobiological mechanisms are still unclear, the available literature mostly seek to explain the positive effects of tVNS on cognitive performance in terms of a change in brain NE levels [ 64 , 108 ].…”
Section: New Possibilitiesmentioning
confidence: 99%
“…A variety of methods have been proposed for the removal of artifacts in taVNS-EEG/MEG recordings. These include notch filtering (Chen et al, 2023; Lloyd et al, 2023; Sharon et al, 2021), independent component analysis (ICA) (Gurtubay et al, 2023), the Cleanline algorithm (Poppa et al, 2022), linear interpolation (Schuerman et al, 2021), and autoregressive modelling (Keatch et al, 2023). A lack of thoroughly evaluated artifact correction methods is recognized as a current challenge for concurrent taVNS-M/EEG studies (Wienke et al, 2023).…”
Section: Introductionmentioning
confidence: 99%